2017
DOI: 10.1002/cbf.3302
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of histone methylation in osteoblastic differentiation of human periosteum‐derived cells cultured in vitro under hypoxic conditions

Abstract: Although oxygen concentrations affect the growth and function of mesenchymal stem cells (MSCs), the impact of hypoxia on osteoblastic differentiation is not understood. Likewise, the effect of hypoxia-induced epigenetic changes on osteoblastic differentiation of MSCs is unknown. The aim of this study was to examine the in vitro hypoxic response of human periosteum-derived cells (hPDCs). Hypoxia resulted in greater proliferation of hPDCs as compared with those cultured in normoxia. Further, hypoxic conditions y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
(91 reference statements)
1
13
0
1
Order By: Relevance
“…Flow cytometry (FACSCalibur, Becton Dickinson, CA, USA) was used to detect surface antigens on DFSCs (1 × 10 5 cells per marker). Specifically, cells were analyzed for the presence of mesenchyme markers (CD44, CD73, CD90, and CD105) and the absence of the hematopoietic markers CD34 and CD45, as described previously 25 . DFSCs that were at approximately 90% confluence were trypsinized, fixed in 3.7% formaldehyde solution, and incubated with fluorescein isothiocyanate (FITC)-conjugated primary antibodies (mouse anti-human) against CD34 (BD Pharmingen, CA, USA), CD44 (BD Pharmingen), CD45 (Santa Cruz Biotechnology, Santa Cruz, CA, USA), and CD90 (BD Pharmingen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry (FACSCalibur, Becton Dickinson, CA, USA) was used to detect surface antigens on DFSCs (1 × 10 5 cells per marker). Specifically, cells were analyzed for the presence of mesenchyme markers (CD44, CD73, CD90, and CD105) and the absence of the hematopoietic markers CD34 and CD45, as described previously 25 . DFSCs that were at approximately 90% confluence were trypsinized, fixed in 3.7% formaldehyde solution, and incubated with fluorescein isothiocyanate (FITC)-conjugated primary antibodies (mouse anti-human) against CD34 (BD Pharmingen, CA, USA), CD44 (BD Pharmingen), CD45 (Santa Cruz Biotechnology, Santa Cruz, CA, USA), and CD90 (BD Pharmingen).…”
Section: Methodsmentioning
confidence: 99%
“…The activity of alkaline phosphatase (ALP), an early marker for osteoblast differentiation, and mineralized nodule formation (indicative of maturation of the osteoblast phenotype) were used as indicators of osteoblast differentiation. ALP activity, alizarin red S and von Kossa staining, and calcium content were examined using a previously published method 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients provided informed consent prior to the collection of periosteal tissues, as required by the Ethics Committee at Gyeongsang National University Hospital. h PDCs were cultured using a previously described technique (Kim et al, ; Yoon et al, ). Periosteal tissues were cultured in 100‐mm culture dishes in Dulbecco's Modified Eagle Medium supplemented with 10% fetal bovine serum, 100 IU/mL penicillin, and 100 μg/mL streptomycin, at 37 °C in 95% humidified air and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work demonstrated that these human periosteum-derived cells (hPDCs) were positive for markers present in MSCs (CD44, CD73, CD90, and CD105) and expressed the pluripotent transcriptional factors Oct4, Nanog, and Sox-2. Moreover, these hPDCs were successfully differentiated into mesenchymal lineages, particularly adipocytes, osteocytes, and chondrocytes; thus, they can be considered to be human periosteum-derived MSCs [17,18].…”
Section: Introductionmentioning
confidence: 99%